The Role of Calmodulin vs. Synaptotagmin in Exocytosis - Xue, Renhao; Meng, Hao; Yin, Jiaxiang; Xia, Jingyao; Hu, Zhitao; Liu, Huisheng (Frontiers in Molecular Neuroscience, 2021)
Exocytosis is a Ca2+-regulated process that requires the participation of Ca2+ sensors. In the 1980s, two classes of Ca2+-binding proteins were proposed as putative Ca2+ sensors: EF-hand protein calmodulin, and the C2 domain protein synaptotagmin. In the next few decades, numerous studies determined that in the final stage of membrane fusion triggered by a micromolar boost in the level of Ca2+, the low affinity Ca2+-binding protein synaptotagmin, especially synaptotagmin 1 and 2, acts as the primary Ca2+ sensor, whereas calmodulin is unlikely to be functional due to its high Ca2+ affinity. However, in the meantime emerging evidence has revealed that calmodulin is involved in the earlier exocytotic steps prior to fusion, such as vesicle trafficking, docking and priming by acting as a high affinity Ca2+ sensor activated at submicromolar level of Ca2+.. Calmodulin directly interacts with multiple regulatory proteins involved in the regulation of exocytosis, including VAMP, myosin V, Munc13, synapsin, GAP43 and Rab3, and switches on key kinases, such as type II Ca2+/calmodulin-dependent protein kinase, to phosphorylate a series of exocytosis regulators, including syntaxin, synapsin, RIM and Ca2+ channels. Moreover, calmodulin interacts with synaptotagmin through either direct binding or indirect phosphorylation. In summary, calmodulin and synaptotagmin are Ca2+ sensors that play complementary roles throughout the process of exocytosis. In this review, we discuss the complementary roles that calmodulin and synaptotagmin play as Ca2+ sensors during exocytosis.